Meningkatkan Aktivitas Belajar, Motivasi dan Keterampilan Berpikir Kritis Siswa Muatan IPA Menggunakan Model PANTING Memakai Media Lilin Siswa Sekolah Dasar - Fadhilah, Akhmad; Suriansyah, Ahmad (Institut Agama Islam Negeri (IAIN) Curup, 2024)
This research was motivated by the low learning outcomes of Science Content students at SDN Kelayan Barat 3, Banjarmasin City. This study aims to increase learning activity, motivation, and critical thinking skills of VB class students at SDN Kelayan Barat 3 Banjarmasin City in science learning content, carried out in the even semester of the 2022/2023 school year. This research is a classroom action research. The results show the acquisition of a classical score on teacher activity at the first meeting gets a percentage of 69.45%, the second meeting 77.8%, the third meeting 86.11%, and the fourth meeting 94.45%. Student motivation at the first meeting was 59.10%, the second meeting was 77.26%, the third meeting was 90.90%, and the fourth meeting was 100%. In student activity the score was 45.45% at the first meeting, the second meeting was 68.18%, the third meeting was 90.90%, and the fourth meeting was 100%. Critical thinking skills at the first meeting scored 45.46%, the second meeting 54.54%, the third meeting 77.27%, and the fourth meeting 100%. In the first meeting student learning outcomes get a score of 45%, the second meeting 59%, the third meeting 77%, and the fourth meeting 100%. This proves that there has been an increase in learning activity, motivation, and critical thinking skills of science content students using wax media using the PANTING model.